L’analyse économique est-elle intemporelle ? - Antoine Parent (Temporalités)
To answer this question, we develop three issues: first, the assessment of the future is the core issue in studying expectations; second, dynamic economic modeling often leads to represent Time as a series of economic equilibriums; lastly, the « New Economic History » investigates History using the rational behavior hypothesis. In that way, the three dimensions of Time, past, present, and future are taken into account by Economic Analyses.